Implementasi Manajemen Pembelajaran Mendalam di SMP Negeri Nawi Abua 1 - Gatot Sukarno Putra; Yulius Mataputun; Petrus Irianto; Indah S. Budiarti; Juliana Waromi; Ida M. Hutabarat (Pusdikra Publishing, 2026)
This study analyzes the implementation of deep learning management to prepare the golden generation at Nawi Abua 1 Public Junior High School, Lanny Jaya Regency. Informants consisted of the principal, teachers, students, education office, committee, and curriculum deputy. The study used a descriptive qualitative method with data collection through deep interviews, participatory observation, and documentation study. Data validity was ensured by triangulation of sources and techniques, while analysis was conducted interactively through data reduction, presentation, and conclusion drawing. The results show the implementation of deep learning management through four aspects: planning (identification of student readiness, teaching modules, diagnostic assessments), organization (division of tasks, roles and responsibilities), implementation (learning objectives, learning activities, learning environment, partnerships), and evaluation (summative, formative, self-evaluation). Supporting factors include teacher qualifications, government policies, contextual learning, technology, and partnerships, while obstacles include limited facilities, learning environments, and students' intellectual abilities. The positive impacts include learning principles, learning experiences, improved 21st-century skills, teachers becoming facilitators, students becoming more active, and improved character. This study contributes to the development of deep learning management practices at Nawi Abua 1 Public Junior High School based on the local 3T context, providing evidence that this approach is effective in preparing the golden generation. There has been limited research on the implementation of deep learning management in mountainous regions with constrained infrastructure and human resources, such as Lanny Jaya Regency, as most previous studies have focused on urban schools.